2014
DOI: 10.1093/mnras/stu2433
|View full text |Cite
|
Sign up to set email alerts
|

HST hot-Jupiter transmission spectral survey: haze in the atmosphere of WASP-6b

Abstract: We report Hubble Space Telescope (HST) optical to near-infrared transmission spectroscopy of the hot Jupiter WASP-6b, measured with the Space Telescope Imaging Spectrograph (STIS) and Spitzer's InfraRed Array Camera (IRAC). The resulting spectrum covers the range 0.29 − 4.5 µm. We find evidence for modest stellar activity of WASP-6 and take it into account in the transmission spectrum. The overall main characteristic of the spectrum is an increasing radius as a function of decreasing wavelength corresponding t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(156 citation statements)
references
References 80 publications
12
143
1
Order By: Relevance
“…For this reason, we performed a two-color monitoring campaign for HAT-P-19 using the 1.2 m telescope STELLA on Tenerife over a time span of about 300 days. Similar studies can be found in the literature for the hot-Jupiter host stars HD 189733 , WASP-19 (Huitson et al 2013), WASP-12 ), HAT-P-1 (Nikolov et al 2014), WASP-6 (Nikolov et al 2015), and WASP-31 . This paper is structured as follows: Sect.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…For this reason, we performed a two-color monitoring campaign for HAT-P-19 using the 1.2 m telescope STELLA on Tenerife over a time span of about 300 days. Similar studies can be found in the literature for the hot-Jupiter host stars HD 189733 , WASP-19 (Huitson et al 2013), WASP-12 ), HAT-P-1 (Nikolov et al 2014), WASP-6 (Nikolov et al 2015), and WASP-31 . This paper is structured as follows: Sect.…”
Section: Introductionsupporting
confidence: 89%
“…Murgas et al (2014) presented a probable detection of Na for WASP-43b and a tentative detection of K was given by Nikolov et al (2015). The (low-resolution) non-detection in the atmospheres of HD 189733b and WASP-12b can be explained by scattering particles blocking the atmospheric heights that are possible for atomic sodium and potassium (Pont et al 2008;Sing et al 2013).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…We demonstrated the feasibility of this technique in a pilot study on WASP-6b (Jordán et al 2013), which precisely measured the optical transmission spectrum of that transiting hot Jupiter in a single transit with Magellan/IMACS, despite strongly variable transparency during part of the transit. The resulting spectrum for WASP-6b was most consistent with scattering, a result confirmed later by HST (Nikolov et al 2015;Sing et al 2016). …”
Section: Accesssupporting
confidence: 70%
“…However, it is worth noting that an increase in planetary radius towards UV wavelengths has been detected for a number of planets, for instance, GJ3470b (Nascimbeni et al 2013;Biddle et al 2014), WASP-6b (Nikolov et al 2015), and WASP-31b . Interestingly, the host stars of all these planets and that of HD 189733b are active stars.…”
Section: Other Interpretations Of the Slopementioning
confidence: 99%